CRITICAL ANALYSIS IN MALPRACTICE AND ITS EFFECTS ON THE HEALTHCARE ADMINISTRATION - 1Jaber Modkhel S Almutairi, 2Omran Abdullah Almutairi, 3Ghala Rseed Alsaihaimi, 4Tariq Eid M Alharbi, 5Munayfah Awad Abdulaziz Alanazi, 6Ahmed Matar Almutairi (Chelonian Research Foundation, 2022)
Malpractice poses a significant challenge in healthcare and affecting patients. This article analyzes its recommendations for a prosperous organization through a comprehensive composition study. Various points and causes of remedial misbehavior are investigated, including helpful misbehavior, dejected communication, and disillusionment. Procedures to diminish disadvantage threats and make stride control are discussed approximately. Revelations are shown in pictures, words, and charts that lay out the complexity and influence of prosperity organizations. Recommendations for tending to restorative misbehavior issues are publicized, checking moving forward communication, executing fruitful risk management procedures, and pushing for genuine reform. Keywords: malpractice, Healthcare Administration, patient safety, risk management, Litigation